As chuvas no estado do Pará, Brasil: classificação climática de abordagem geográfica - Soares, Lucas Pereira (2023)
This work was developed based on the theoretical-methodological framework shaped by Geographic Climatology, following the guidelines offered by geographer Carlos Augusto de Figueiredo Monteiro, who proposes an understanding of rainfall and its relationship with atmospheric dynamics, together with surface factors, aiming to a genetic and geographic climate classification, based on the rhythm of succession of weather types. The state of Pará was chosen as the study area due to its climatic and geomorphological particularities, as well as the lack of regional studies based on Geographic Climatology. To progress the research, an analysis was carried out on atmospheric dynamics, and the rainfall associated with it for the state of Pará, considering the election of “standard years” in the period 1990 to 2019, in order to develop a climate classification proposal genetic, rhythmic and geographic. From this general approach, the steps outlined by Monteiro (1973) were applied, which advocate: the daily synoptic analysis of “standard years”, the advent of participation rates and the characterization of geographic factors. With the development of these, it was possible to present the classification proposal, guided by the establishment of regions of dominance of atmospheric systems, through participation indices and their synthesis, and from the association with Strahler's regional classification (1978). The constitution of this was also permeated by rainfall zoning by homogeneous groups which, in association with superficial geographic factors and the characterization by participation rates, allowed the classification of local climates. Thus, the climate classification for the state of Pará was created. In a proposal that, at the regional level and designed based on Geographic Climatology, consists of the first work for the state, enriching, from this, the list of analyzes on climatic conditions dynamics, in an extremely important region and routinely included in global agendas regarding changes in the planet's current climate pattern.